The Effect of Jigsaw-Type Cooperative Learning on Motor Skills and Basic Sepak Takraw Techniques in Students - Bachtiar, Ishak; Adil, Ahmad (Sains Global Institut, Indonesia, 2025)
This study aimed to analyze the effect of the Jigsaw cooperative learning model on motor skills and basic Sepak Takraw techniques in students at SMPN 13 Makassar. The study used a one-group pretest-posttest design with a sample of 40 students. The instruments used included motor skills tests (agility, coordination, reaction speed, balance) and basic Sepak Takraw techniques tests (serving, control, passing, footwork, and ball contact accuracy). The results showed a significant improvement after implementing the Jigsaw model. For motor skills, the average score increased from 63.20 (pretest) to 78.55 (posttest), representing a 15.35-point increase. A paired sample t-test showed a p-value of 0.000, indicating a significant difference before and after the treatment. The effect size, calculated using Cohen's d, was 1.89, categorized as a very large effect. In the basic Sepak Takraw technique test, the average score increased from 61.64 (pretest) to 78.80 (posttest), representing a 17.16-point increase. All technical components improved, particularly footwork, which increased by 18.5 points. The statistical test results showed a p-value of 0.000, with an effect size of 2.12, which is also considered very large. Overall, the Jigsaw cooperative learning model has proven effective in improving the motor skills and basic Sepak Takraw technical skills of junior high school students. These findings recommend Jigsaw as an alternative learning model capable of improving the quality of Physical Education (PJOK) learning, particularly in Sepak Takraw.